OPTIMIZING ELECTRICITY SUBSIDIES: A TOPSIS-BASED DECISION-MAKING APPROACH - Amin, Ruhul; Christian, Ade; Radiyah, Ummu; Sumanto, Sumanto; Hariyanto, Hariyanto; Yani, Ahmad (Jurnal Teknoinfo, 2024)
A individual or household is said to be in poverty if their income is insufficient to cover even the most basic requirements. According to BPS, 40% of Indonesians live in the country with the weakest economy. The use of power subsidies is one of the government's strategies for combating poverty. To combat poverty, the government works with PT. PLN to implement an electrical subsidy scheme that distributes payments to disadvantaged neighborhoods. The goal of the subsidy is to ensure the availability of power while assisting underprivileged customers and those who haven't heard from PT. PLN so they may take part in enjoying electrical energy. However, there are still challenges when there are several procedures, which makes it difficult to make judgments since they must take into account numerous factors. Using TOPSIS to solve 10 possibilities, including the following, is one way to get around the FMADM's various requirements: job, income, dependents, vehicle assets, home ownership, building area, source of drinking water, electrical power range, kind of floor, and type of house wall. According to the study's precise findings, only 11 residents out of 20 submissions received immediate recommendations for receiving power subsidies without having to wait a lengthy period. Additionally, although 9 people received recommendations for aid, only 1 received a recommendation against receiving support.